2002
DOI: 10.1381/096089202762252398
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Morbid Obesity with Intragastric Balloon in Association with Diet

Abstract: The best indications for BIB were: morbidly obese opatients (BMI > 40) and super-obese patients (BMI > 50) in preparation for bariatric operations; obese patients with BMI 35-40 with co-morbilities in preparation for bariatric surgery; obese patients with BMI 30-35 with a chronic disease otherwise unresolved; patients with BMI < 30 only in a multidisciplinary approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 10 publications
3
53
1
4
Order By: Relevance
“…Previously published results revealed an average weight loss of 12-15 kg over 6 months with an excellent safety profile [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The Spatz Adjustable balloon was introduced in 2010 as the first IGB approved for 1 year implantation while featuring an adjustability function that afforded balloon volume changes as needed.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published results revealed an average weight loss of 12-15 kg over 6 months with an excellent safety profile [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The Spatz Adjustable balloon was introduced in 2010 as the first IGB approved for 1 year implantation while featuring an adjustability function that afforded balloon volume changes as needed.…”
Section: Introductionmentioning
confidence: 99%
“…Balloon tolerability was very good in our series; we did not have to remove any balloon before the determined time and this is better than that published in the literature, which describes 4.2-11% of patients who required balloon removal due to lack of tolerability or complications (24,(27)(28)(29)32).…”
Section: Discussionmentioning
confidence: 49%
“…Other authors have found that pre-surgical weight loss is a predictive factor for a higher loss weight during post-surgical evolution (6,17), and would help to select those obese population who would benefit most from bariatric surgery. The IGB in morbid obesity is a temporal treatment given as a second step when the multidisciplinary nutritional treatment fails (23), because it results in greater weight loss compared to conventional diet treatments (24)(25)(26)(27), although it is not clear whether it is more effective (28,29).…”
Section: Obesity (Bmi ≥ 30 Kg/mmentioning
confidence: 99%
See 2 more Smart Citations